Evaluation of LRIG1 expression in larynx pathologies - CİNEL, ZELİHA LEYLA; YUMUŞAKHUYLU, ALİ CEMAL (My University, 2022)
Objective: Studies have been performed on many biomolecules to determine the prognosis of LSCC and predict the course of the disease. However, a molecular marker that can be used clinically has not yet been found. Therefore, in this study, we aimed to investigate the expression levels of LRIG 1 in laryngeal cancer. Materials and Methods: In our study, 219 cases who underwent surgery due to LSCC and 88 randomly selected patients whose pathologic result were benign and premalignant lesions in Marmara University Pendik Education and Research Hospital between 2003 and 2018 were analyzed. Patients’ data were obtained from the medical records. The tissue microarray method was used to evaluate specimens. Results: There was a statistically significant difference between the tumor differentiation, diagnosis, and the expression of LRIG1 (respectively p=0.045, p<0.001). Also, an increase in the degree of dysplasia in premalignant lesions correlates with a decrease in LRIG1 expression (p=0.015). Conclusion: Our findings suggest that LRIG1 plays a role in the early tumorigenesis of LSCC. Therefore, LRIG1 can be a target molecule for treatment approaches. However, LRIG1 was not correlated with overall survival of the LSCC.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Laryngeal carcinoma; tumorigenesis; LRIG1